2007
DOI: 10.1002/cncr.22836
|View full text |Cite
|
Sign up to set email alerts
|

Differences in breast carcinoma characteristics in newly diagnosed African–American and Caucasian patients

Abstract: A convenient and cost‐effective strategy for synthesis of hyperbranched poly(ester‐amide)s from commercially available dicarboxylic acids (A2) and multihydroxyl secondary amine (CB2) has been developed. By optimizing the conditions of model reactions, the AB2‐type intermediates were formed dominantly during the initial reaction stage. Without any purification, the AB2 intermediate was subjected to thermal polycondensation in the absence of any catalyst to prepare the aliphatic and semiaromatic hyperbranched po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
172
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(198 citation statements)
references
References 66 publications
9
172
0
6
Order By: Relevance
“…BCA treatment is becoming more personalized for patients [42]. Being able to document the nuances of a patient's personalized treatment regimens may be even more critical in AABCS because of the higher rates of triple-negative BCA diseases and late stage diagnoses among African Americans compared to their White counterparts [1,43,44]. The treatment of these cancers may require differing or more aggressive treatments, resulting in increased concerns about treatment side effects and medication regimens.…”
Section: Discussionmentioning
confidence: 99%
“…BCA treatment is becoming more personalized for patients [42]. Being able to document the nuances of a patient's personalized treatment regimens may be even more critical in AABCS because of the higher rates of triple-negative BCA diseases and late stage diagnoses among African Americans compared to their White counterparts [1,43,44]. The treatment of these cancers may require differing or more aggressive treatments, resulting in increased concerns about treatment side effects and medication regimens.…”
Section: Discussionmentioning
confidence: 99%
“…[710] However, this observation contradicts the overwhelming evidence that African-American women are diagnosed with more aggressive clinical and biological behavior of invasive breast cancer. [2, 3, 18] Most likely this reason is multifold. First, socioeconomic status and access barriers to health care may be one reason.…”
Section: Discussionmentioning
confidence: 99%
“…Crabb et al [21] investigated axillary nodal involvement in 4,444 early-stage BC cases and showed that the basal-like subtype predicts a lower incidence of axillary nodal involvement, which is in agreement with our study. In addition, studies of triple-negative BC revealed marked heterogeneity within this group, and gene expression profiling is important for inter-group discrimination [22,23,24]. Despite the poor survival data, the lower LNR may have arisen from this heterogeneity, a fact that should be considered in future genetic studies.…”
Section: Discussionmentioning
confidence: 99%